PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK DENGAN MODEL PROBLEM BASED LEARNING PADA POKOK BAHASAN BANGUN RUANG SISI DATAR - Wirasyid Hafizul Lathief (Departemen Matematika, 2021)
The purpose of this study was to develop student worksheets (LKPD) a polyhedron topic for class VIII SMP with a scientific approach applied to cooperative learning model type Problem Based Leaming (PBL) which is valid and practical. This study uses the Plomp development model which consists of three phases, namely the preliminary research phase, a prototyping phase, and an assessment phase. In preliminary research, needs analysis, curiculum analysis, concept analysis and student analysis. The prototyping phase is the stage of designing learning tools consisting of prototype 1, prototype 2, prototype 3, and prototype 4. The last step is the next step in confirming the practicality of the LKPD through the results of the student practicality questionnaire. According to the results of validity data analysis, LKPD based on a scientific approach using PBL model has been shown to have a validity level of 82.72% in a very valid category. The test results data from the student survey of the practicality questionnaire accounted for 93,2% of the very practical category. It can be concluded that LKPD based on a scientific approach with the PBL model on polyhedron topic for students of class VIII SMP can be categorized valid and practical. Keywords — Development Research, Student Worksheet, Scientific Approuach, Problem Based Leaming